2017
DOI: 10.1002/2017jb014046
|View full text |Cite
|
Sign up to set email alerts
|

Fluid migration in the mantle wedge: Influence of mineral grain size and mantle compaction

Abstract: Mineral grain size in the mantle affects fluid migration by controlling mantle permeability; the smaller the grain size, the less permeable the mantle is. Mantle shear viscosity also affects fluid migration by controlling compaction pressure; high mantle shear viscosity can act as a barrier to fluid flow. Here we investigate for the first time their combined effects on fluid migration in the mantle wedge of subduction zones over ranges of subduction parameters and patterns of fluid influx using a 2‐D numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 61 publications
5
79
1
Order By: Relevance
“…The effect of fluid pressure on frictional yield, which may weaken for instance the subduction interface and lead to dehydration embrittlement (Jung et al, ; Podladchikov & Miller, ; Skarbek & Rempel, ), is also missing from our models. Lastly, future models could include grain‐size‐dependent and anisotropic permeability, which may play a role in the development of the fluid pathways in subduction zones (Cerpa et al, ; Kawano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fluid pressure on frictional yield, which may weaken for instance the subduction interface and lead to dehydration embrittlement (Jung et al, ; Podladchikov & Miller, ; Skarbek & Rempel, ), is also missing from our models. Lastly, future models could include grain‐size‐dependent and anisotropic permeability, which may play a role in the development of the fluid pathways in subduction zones (Cerpa et al, ; Kawano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Permeability is generally proportional to / n where n ranges from 2 to 3. We use n 5 2 in equation (6), although we investigate the effects of different value for n in Appendix C. Note that although the spatial and temporal variations in grain size also affect permeability (e.g., Cerpa et al, 2017;Wada & Behn, 2015), we do not consider the effect here. Fluid viscosity is given as a function of temperature and also the concentration of dissolved silicate, which increases significantly with pressure (from about 30 wt % at 3 GPa to about 70 wt % at 8 GPa; Mibe et al, 2002).…”
Section: Numerical Approachmentioning
confidence: 99%
“…These include the effects of dynamic pressure caused by shear deformation of matrix (e.g., Faccenda et al, 2009Faccenda et al, , 2012Spiegelman & McKenzie, 1987), hydration-dehydration reactions and melting (Iwamori, 1998), compaction (Cerpa et al, 2017;Wilson et al, 2014), grain size distribution (Cerpa et al, 2017;Wada & Behn, 2015), and 3-D slab geometry combined with permeability anisotropy (Morishige & van Keken, 2017). These include the effects of dynamic pressure caused by shear deformation of matrix (e.g., Faccenda et al, 2009Faccenda et al, , 2012Spiegelman & McKenzie, 1987), hydration-dehydration reactions and melting (Iwamori, 1998), compaction (Cerpa et al, 2017;Wilson et al, 2014), grain size distribution (Cerpa et al, 2017;Wada & Behn, 2015), and 3-D slab geometry combined with permeability anisotropy (Morishige & van Keken, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we developed numerical models of fluid migration in the mantle wedge accounting for both grain-size distribution and mantle compaction (Cerpa et al, 2017). The modeling results showed that spatial variations of grain size and solid shear viscosity both serve to focus fluids beneath the arc, and that their contributions as fluid-focusing mechanisms vary spatially in the mantle wedge.…”
Section: Introductionmentioning
confidence: 99%